Identification of Potential MHC Class-II-Restricted Epitopes Derived from Leishmania donovani Antigens by Reverse Vaccinology and Evaluation of Their CD4+ T-Cell Responsiveness against Visceral Leishmaniasis - Dikhit, Manas Ranjan; Kumar, Akhilesh; Das, Sushmita; Dehury, Budheswar; Rout, Ajaya Kumar; Jamal, Fauzia; Sahoo, Ganesh Chandra; Topno, Roshan Kamal; Pandey, Krishna; Das, V. N. R.; Bimal, Sanjiva; Das, Pradeep (Frontiers in Immunology, 2017)
Visceral leishmaniasis (VL) is one of the most neglected tropical diseases for which no vaccine exists. In spite of extensive efforts, no successful vaccine is available against this dreadful infectious disease. To support vaccine development, an immunoinformatics approach was applied to screen potential MHC class II restricted epitopes that can activate the immune cells. Initially, 37 epitopes derived from six stage-dependent, over-expressed antigens were predicted, which were presented by at least 26 diverse MHC class II allele. Based on a population coverage analysis and HLA cross presentation ability, six of the 37 epitopes were selected for further analysis. Stimulation with synthetic peptide alone or as a cocktail triggered intracellular IFN-γ production. Moreover, a specific IgG class of antibodies was detected in the serum of active VL cases against P1, P4, P5 and P6 in order to evaluate the peptide effect on the humoral immune response. Additionally, most of the peptides, except P2, were found to be non-inducers of CD4+ IL-10 against both active VL as well as treated VL subjects. This finding suggests there is no role of these peptides in the pathogenesis of Leishmania. Peptide immunogenicity was validated in BALB/c mice immunized with a cocktail of synthetic peptide emulsified in complete Freund’s adjuvant/incomplete Freund’s adjuvant. The immunized splenocytes induced strong spleen cell proliferation upon parasite re-stimulation. Furthermore, increased IFN-γ, IL-12, IL-17 and IL-22 production augmented with elevated nitric oxide (NO) synthesis is thought to play a crucial role in macrophage activation. In this investigation, we identified six MHC class II-restricted epitope hotspots of Leishmania antigens that induce CD4+ Th1 and Th17 responses, which could be used to potentiate a human universal T-epitope vaccine against visceral leishmaniasis.